Effect of morphed trailing-edge flap on aerodynamic load control for a wind turbine blade section. (April 2020) - Zhuang, Chen; Yang, Gang; Zhu, Yawei; Hu, Dean
Abstract: Application of Morphed Trailing-Edge Flap (MTEF) can significantly reduce the excessive loads that cause damage of blades and surrounding components in wind turbine. The present paper investigates the effect of MTEF on the aerodynamic load control of a large-scale wind turbine blade. Three design parameters that control MTEF kinematics, such as deflection length, amplitude and phase shift, are analyzed in detail by a validated Computational Fluid Dynamic (CFD) model, in which a specially-designed mesh update method is adopted. Results show that, compared with fully rigid airfoil, the morphed airfoil exhibits an excellent load control capability owing to the appropriate change of aft effective camber as deflection motion of MTEF, which significantly alters the pressure distribution and air flow. Furthermore, the performances are linearly improved with increasing MTEF deflection length, wherein every 0.1 c increase in length results in the percentage variation of C L, min (+45%), C L, max (−3%), C D, max (−5%) and C L / C D (+30%). Whereas the improved performance due to the increase of deflection amplitude shows a reducing trend, and an oversize deflection amplitude (greater than β amp  = 10°) leads to the depravation of aerodynamic efficiency. Moreover, the analysis of deflection phase shift suggests that a slight phase–lag is beneficial to stabilize the aerodynamic load exerted on wind turbine blade. Especially, the lift coefficient fluctuation ( C L, max − C L, min ) for the phase-lag case of φ  = 1/8π has reduced by about 50% while the cycle-averaged lift coefficient has increased by 16.67% as compared to the fully rigid airfoil. The results of this paper will help guide future development and application of MTEF in practice. Highlights: Effects of MTEF on the aerodynamic load control for a turbine blade are investigated. A specially-designed mesh update method is applied to achieve smooth mesh deformation. Load control ability is linearly improved with increasing deflection length. An oversize deflection amplitude leads to the depravation of aerodynamic efficiency. Slight phase–lag of MTEF can stabilize the aerodynamic load on wind turbine blade.